Kinerja tingkat pengembalian saham batu bara dalam isu krisis energi - Poae, Meilan; Manangka, Theresia Maria (Riset Akuntansi dan Manajemen Pragmatis, 2023)
The condition of the Indonesian capital market at the beginning of 2023 is filled with the issue of the energy crisis. This condition began with the phenomenon of a decline in the world coal index which was accompanied by a downward trend in stock market prices. This study aims to examine the return performance of coal issuers in the energy crisis issue in the period January to April 2023. This study finds that the return from coal stocks is highest in March 2023, but overall performance is still not optimal. This is supported by findings that show that returns inter-months are not significantly different. This study also finds that returns and the world coal index tend to have an insignificant and small relationship. Apart from that, the correlation coefficient also shows a positive value, indicating that an increase in the world coal index will be followed by an increase in returns.